From the Invisible Handshake to the Invisible Hand? How Import Competition Changes the Employment Relationship - Bertrand, Marianne (Journal of Labor Economics, 2004)
Does import competition alter the extent to which employers, after negotiating workers’ wages upon hire, subsequently shield those wages from external labor‐market conditions? If increased competition induces a switch away from these wage implicit agreements, then (1) the sensitivity of workers’ wages to the current unemployment rate should increase as competition increases and (2) the sensitivity of workers’ wages to the unemployment rate prevailing upon hire should decrease. Using exchange‐rate movements to generate exogenous variation in import competition, I find evidence supporting both of these predictions. I show that increased financial pressures on employers is one mechanism driving these effects.